Probing Dynamic Features of Phagosome Maturation in Macrophage using Au@MnO x @SiO 2 Nanoparticles as pH‐Sensitive Plasmonic Nanoprobes - Shang, Jinhui; Yang, Qian; Fan, Wenjun; Chen, Yancao; Tang, Decui; Guo, Haowei; Xiong, Bin; Huang, Shuangyan; Zhang, Xiao‐Bing (Chemistry, an Asian journal, 2021)
Phagosome maturation in macrophage is essential to the clearance of pathogenic materials in host defence but the dynamic features remain difficult to be measured in real time. Herein, we reported the multilayered Au@MnO x @SiO 2 nanoparticle as a robust pH‐sensitive plasmonic nanosensor for monitoring the dynamic acidification features over the phagosome maturation process in macrophage under darkfield microscopy. For this multilayered nanosensor, the gold nanoparticle core plays a role of signal reporter, the MnO x shell and the outmost SiO 2 act as the sensing layer and the protecting layer, respectively. After subject to the acidic buffer solution, the MnO x layer in the multilayered nanoprobe could be decomposed rapidly, resulting in a remarkable spectral shift and color change under darkfield microscopy. We demonstrated this nanosensor for the investigation of single phagosome acidification dynamics by monitoring the color changes of nanoprobes after phagocytosis over time. The nanoprobes after phagocytosized in macrophage displayed a slight color change within the first hour and then cost several minutes to change from red to green in the next stage, indicating the phagosome undergoes a slow first and then fast acidification feature as well as a slow‐to‐fast acidification translation over the phagosome maturation process. Moreover, we validated that the slow‐to‐fast acidification translation was dependent on the activation of V‐ATPase from the ATP depletion assay. We believed that this nanosensor is promising for studying the dynamic acidification features as well as disorders in phagosome maturation in phagocytic cells, which might provide valuable information for understanding the disease pathogenesis related to phagosome dysfunctions.